Reliability of Selective Laser Melted AlSi12 Alloy for Quasistatic and Fatigue Applications - Siddique, Shafaqat; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Vieweg, 2019)
Selective laser melting (SLM) has established itself as the most prominent additive manufacturing (AM) process for metallic structures in aerospace, automotive and medical industries. For a reliable employment of this process, it has to conform to the demanding requirements of these industries in terms of quasistatic and, especially, fatigue performance. Shafaqat Siddique identifies the influence of SLM processing conditions on the microstructural features, and their corresponding influence on the mechanical behavior of the processed AlSi12 alloy structures. The author also gives insight into integrated manufacturing by combining conventional and SLM processes to get the synergic benefits. Requirements for fatigue-resistant designs in additive manufacturing are highlighted, and a novel method is developed for agile fatigue life prediction. Contents State of the art and investigation methodology Characterization, quasistatic and fatigue behavior of AlSi12 alloy Hybrid AlSi12 alloy structures Fatigue prediction methodology Target Groups Students and lecturers in mechanical, manufacturing and materials engineering Research and design engineers in additive manufacturing About the Author Shafaqat Siddique worked as Scientific Assistant at Technical University Dortmund, Department of Materials Test Engineering (WPT), and completed his Ph.D. research in cooperation with Laser Zentrum Nord (LZN) in Hamburg. He continues his post-doctoral research at TU Dortmund, Germany.
State of the art and investigation methodology -- Characterization, quasistatic and fatigue behavior of AlSi12 alloy -- Hybrid AlSi12 alloy structures -- Fatigue prediction methodology.
Keywords: Materials; Metals; Materials -- Analysis; Materials Engineering; Metals and Alloys; Characterization and Analytical Technique